Contaminants of Emerging Concern in the Lower Volta River, Ghana, West Africa: The Agriculture, Aquaculture, and Urban Development Nexus. (20th January 2022) - Huff Chester, Anndee; Gordon, Christopher; Hartmann, Heather A.; Bartell, Stephen E.; Ansah, Emmanuel; Yan, Tao; Li, Bo; Dampha, Nfamara K.; Edmiston, Paul L.; Novak, Paige J.; Schoenfuss, Heiko L.
Abstract: Contaminants of emerging concern (CECs) are ubiquitous in aquatic environments across all continents and are relatively well known in the developed world. However, few studies have investigated their presence and biological effects in low‐ and middle‐income countries. We provide a survey of CEC presence in the Volta River, Ghana, and examine the microbial consequences of anthropogenic activities along this economically and ecologically important African river. Water and sediment samples were taken by boat or from shore at 14 sites spanning 118 km of river course from the Volta estuary to the Akosombo dam. Sample extracts were prepared for targeted analysis of antimicrobial CECs, N, N ‐diethyl‐meta‐toluamide, and per‐ and polyfluoroalkyl substances (PFAS; water only). Concurrent samples were extracted to characterize the microbial community and antibiotic‐resistant genes (ARGs). Antibiotics and PFAS (PFAS, 2–20 ng/L) were found in all water samples; however, their concentrations were usually in the low nanograms per liter range and lower than reported for other African, European, and North American studies. N, N ‐Diethyl‐meta‐toluamide was present in all samples. The number of different genes detected (between one and 10) and total ARG concentrations varied in both water (9.1 × 10 −6 to 8.2 × 10 −3 ) and sediment (2.2 × 10 −4 to 5.3 × 10 −2 ), with increases in gene variety at sites linked to urban development, sand mining, agriculture, and shellfish processing. Total ARG concentration spikes in sediment samples were associated with agriculture. No correlations between water quality parameters, CEC presence, and/or ARGs were noted. The presence of CECs in the lower Volta River highlights their global reach. The overall low concentrations of CECs detected is encouraging and, coupled with mitigation measures, can stymie future CEC pollution in the Volta River. Environ Toxicol Chem 2022;41:369–381. © 2021 SETAC